2016
DOI: 10.5120/ijca2016911317
|View full text |Cite
|
Sign up to set email alerts
|

Opinion Mining on Twitter Data using Unsupervised Learning Technique

Abstract: Social media is one of the biggest forums to express opinions. Sentiment analysis is the procedure by which information is extracted from the opinions, appraisal and emotions of people in regards to entities, events and their attributes. Sentiment analysis is also known as opinion mining. Opinion mining is to analyze and cluster the user generated data like reviews, blogs, comments, articles etc. These data find its way on social networking sites like twitter, facebook etc. Twitter has provided a very gigantic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Dey et al [13] that explain Naive Bayes is better than other classification methods for hotel review case studies, Suhariyanto et al [14] that explain support-vector machine (SVM) is better than other classification methods for detection fake movie [15], decition tree is better than Naïve Bayes and k-NN [16], k-NN is better than Naïve Bayes [17], k-nearest neighbor classifier is transparent, consistent, straightforward, simple to understand, high tendency to possess desirable qualities and easy to implement than most other machine learning techniques [18]. The process of extracting data sets on social media is more suitable for using unsupervised machine learning than supervised learning [19], subversion (SVN) has the lowest accuracy than k-NN and Naive Bayes [20], sentiment analysis is widely applied in fields related to opinions describing satisfaction or dissatisfaction such as case studies of tourist reviewers, film reviewers and the like [21], [22]. It is these various case studies that produce many conclusions, because each of these cases also uses various datasets, both training data and testing data, so that they have the potential to produce various kinds of conclusions.…”
Section: Related Workmentioning
confidence: 99%
“…Dey et al [13] that explain Naive Bayes is better than other classification methods for hotel review case studies, Suhariyanto et al [14] that explain support-vector machine (SVM) is better than other classification methods for detection fake movie [15], decition tree is better than Naïve Bayes and k-NN [16], k-NN is better than Naïve Bayes [17], k-nearest neighbor classifier is transparent, consistent, straightforward, simple to understand, high tendency to possess desirable qualities and easy to implement than most other machine learning techniques [18]. The process of extracting data sets on social media is more suitable for using unsupervised machine learning than supervised learning [19], subversion (SVN) has the lowest accuracy than k-NN and Naive Bayes [20], sentiment analysis is widely applied in fields related to opinions describing satisfaction or dissatisfaction such as case studies of tourist reviewers, film reviewers and the like [21], [22]. It is these various case studies that produce many conclusions, because each of these cases also uses various datasets, both training data and testing data, so that they have the potential to produce various kinds of conclusions.…”
Section: Related Workmentioning
confidence: 99%
“…Muqtar Unnisa, et al [3] from Darussalam Hyderabad TS. Based on the results of research that has been done, the first research is measuring public opinion with a reasonable assessment in film reviews with a machine learning algorithm based on spectral clustering for sentiment analysis.…”
Section: Related Workmentioning
confidence: 99%
“…Similarly, unsupervised learning methods directly produce positive or negative labelled outputs using different techniques and algorithms such as k- means, TF-IDF and PMI-IR algorithms (Turney, 2002;Zagibalov and Carroll, 2008;Unnisa et al, 2016), but again without a clear interpretation of the classes identified. Lexicon-based approaches (as well as some unsupervised learning methods methods such as Turney (2002)) have proceeded by calculating the semantic orientation (a numerical score) and deciding the polarity of the document depending on its sign and the sentiment strength based on its magnitude.…”
Section: Approaches To Sentiment Classificationmentioning
confidence: 99%